An Empirical Study on Shopping Motivation among Generation Y Indian. Issue 2 (April 2021) - Kumar, Sushant; Sadarangani, Pradip
The purpose of the study is to examine the relationship between shopping motivation and purchase intention. This study examines the impact of antecedents of utilitarian motivation and hedonic motivations on purchase intention among Generation Y Indian. The study follows the quantitative approach and collects the data through the survey questionnaire. A total of 229 responses are collected and analysed by using the structural equation modeling. Both hedonic motivations and utilitarian motivations are found to be influencing the purchase intention of foreign brand clothing. The antecedent of utilitarian motivations customized advertisements, and convenience and the antecedent of hedonic motivations adventure, authority and status are found to be significant. The findings are applicable to marketers as while designing the integrated marketing communications, management may emphases the hedonic dimensions of adventure, authority and status along with the utilitarian dimensions of customized advertisements and convenience for greater impact on consumers. The study contributes to the theory of shopping motivation and generational approach in marketing. The article adds value to the literature not only by validating previous work but also by offering new insights into shopping motivation and Generation Y India.